Exploring the potential of Braingame Brian for executive function improvement in Spanish-speaking children with ADHD: A pilot study (2024)
Considering the implications of executive function (EF) in the core symptoms of attention deficit hyperactivity disorder (ADHD), further research is required on strategies such as therapies, treatments, and rehabilitation programs focused on improving EF. This study aimed to assess the potential of an EF training program called “Braingame Brian” in improving working memory, inhibition, and cognitive flexibility in children with ADHD. The programme was developed in the Netherlands and has been shown to be effective in pilot studies of ADHD populations conducted in this country. However, it has not been used before in the Spanish-speaking population. A total of 41 children (aged 8–12 years) were assigned to the EF training or waitlist control groups. The intervention consisted of a 25-session training programme of approximately 45 min per day for nine consecutive weeks. Treatment outcomes were assessed using cognitive tasks of the trained EF, as well as evaluations of EF behaviors by parents and teachers. The initial findings suggest that the implementation of the Braingame Brian programme may be associated with improvements in working memory, inhibition, and cognitive flexibility. These preliminary results also indicate the potential for enhancements in parents’ and teachers’ perceptions of EF difficulties in children with ADHD.